Effect of Sodium Hydroxide and Mould Shape in Geopolymer Fabrication Made With Synthesised Local Clay for Water Filtration - Bolong, N.; Saad, I.; Arshad, S. E. (Journal of Applied Membrane Science & Technology, 2017)
The preparation and testing of geopolymer ceramic membranes for water separation is presented. Geopolymers are typically used in refractories and as precursors to ceramic formation, allowing the production of ceramic-like materials with low temperature processes. A new geopolymer material was synthesized using local clay from Sabah, Malaysia and its filtration performance was compared to a commercial clay fabrication. The synthesized formulation of geopolymer ceramic paste was made by mixing local metakaolin clay as a source of aluminosilicate with alkaline solution, and then curing in a sealed environment. The amorphous paste was crushed and moulded prior to firing at an elevated temperature up to 700ï‚°C. The feasibility of this laboratory-fabricated geopolymer for water filtration applications was studied by evaluating its performance at different thicknesses and mould shapes of fabricated membrane using 8 to 16 Molar natrium hydroxide (NaOH) as the alkali activator in the synthesis of the geopolymer. The result found that increased molarity of sodium hydroxide results higher compressive strength and affect filtration rate. Improved filtration performance (subject to the shape and width of the geopolymer membrane) was found by analysis and separation rates of 47% for blue dye colour and 88% for turbidity were achieved when operated without pressure or pump.